PENGARUH EFEKTIVITAS PROMOSI MELALUI MEDIA SOSIAL INSTAGRAM TERHADAP MINAT BELI KONSUMEN PADA PRODUK KULINER “GEROBAK ELBA” BANJARMASIN - Marijati Sangen; F. R. Dalimunthe; Meiske Claudia (Universitas Lambung Mangkurat, 2021)
This study aimed to provide an academic justification for the effectiveness of Instagram as a medium to promote the products of Micro, Small and Medium Enterprises (MSMEs) in the food and beverage sector so that people's buying interest and its sales turnover could increase. Primary data was collected through a research questionnaire using Likert scale. The analytical tool used was multiple linear regression which aimed to predict the effect of the effectiveness of promotion through Instagram on consumers buying interest using the AIDA concept (Attention, Interest, Desire, and Attention) for Gerobak Elba culinary products. The research sample was 100 active Instagram account owners acted as Gerobak Elba followers or have ever heard or seen